Tau is required for the function of extrasynaptic NMDA receptors - Pallas-Bazarra, Noemí (Sci Rep, 2019)
Tau is a microtubule-associated neuronal protein found mainly in axons. However, increasing evidence indicates that it is also present in dendrites, where it serves as an essential mediator of synaptic NMDA (N-methyl-D-aspartate) receptor-dependent excitotoxicity. Of note, NMDA receptors can also be found outside synapses in the plasma membrane, and activation of extrasynaptic NMDA receptors has been shown to be more linked to excitotoxicity than the activation of synaptic ones. Little is known about the role of Tau in the activity of extrasynaptic NMDA receptors. Thus, we have used a Tau knockout mouse model (Tau(−/−) mice) to analyze the consequences of Tau absence in extrasynaptic NMDA receptor activity. We demonstrate that absence of Tau leads to a decrease in functional extrasynaptic NMDA receptors in the hippocampus. We propose that this impairment in extrasynaptic NMDA receptor activity may contribute to the well-known neuroprotective effect associated with Tau deficiency under pathological conditions.